Study and application on the size effect and end effect of red sandstone mechanical properties - Feng Chen; Jinyang Du; Yanhong Du; Ruxuan Li; Chun’an Tang; Yishan Pan; Gen Li (Scientific Reports)
Abstract Based on the size effect, end effect, and burst tendency of rocks, this paper designs and conducts a series of uniaxial compression laboratory experiments and numerical simulation experiments to explore the influence of these factors on the mechanical properties of rocks. Dense, hard, and brittle red sandstone was used in the experiments, and specimens with different heights, cross-sectional areas, and cubic volumes were prepared. By measuring stress–strain curves, uniaxial compressive strength, and other physical and mechanical parameters, the effects of size effect on rock strength and failure modes were analyzed. Additionally, the paper discusses the influence of different-sized specimens on the rock burst tendency, introducing a parameter K to evaluate this tendency. The results indicate that the rock burst tendency of different-sized specimens remains stable around 2, with the K value of H150 specimens potentially being higher due to structural instability. Furthermore, numerical simulations using RFPA3D software were conducted to further validate the experimental results and delve into the mechanism of the end effect on the mechanical properties of rock specimens. The results indicate that the compressive strength of specimens increases with their size, and specimens of different sizes exhibit notable differences in failure modes. This paper also designs a novel "enhance strength and reduce rockburst" negative Poisson’s ratio material pad based on the "cyclo-hoop effect" induced by the end effect, aiming to improve the strength of compressed components and reduce the intensity of energy release during failure. This study provides essential insights into understanding rock mechanical properties and their applications in engineering.